The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/17549500903577022
|View full text |Cite
|
Sign up to set email alerts
|

Language development and everyday functioning of children with hearing loss assessed at 3 years of age

Abstract: This paper reports language ability and everyday functioning of 133 children with hearing impairment who were evaluated at 3 years of age, as part of the Longitudinal Outcomes of Children with Hearing Impairment (LOCHI) study. The language abilities of children were evaluated using the Preschool Language Scale (PLS-4), Peabody Picture Vocabulary Test (PPVT), Diagnostic Evaluation of Articulation and Phonology (DEAP) and Child Development Inventory (CDI). Everyday functioning of children was evaluated by interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 29 publications
3
51
0
4
Order By: Relevance
“…In fact, among multiple factors affecting developmental outcomes of children with hearing impairment, the effect of timing of intervention is considered the minimal as compared with other demographic factors related to the child and family [13,27] .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, among multiple factors affecting developmental outcomes of children with hearing impairment, the effect of timing of intervention is considered the minimal as compared with other demographic factors related to the child and family [13,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Children with mothers who showed better communication skills with them had more speaking and reading scores and less behavioral problems [36]. Ching et al reported that the educational level of parents of children with hearing loss has significant effects on language output [33]. The greatest progress was seen in children whose families had the highest level of participation in the early intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the age of children at intervention and the role of parents, other factors such as educational status, use of sign language in the home, intelligence, use of hearing aids, and hearing impairment starts, may also cause differences between the hearing-impaired children and normal children [23,33]. Therefore, it is essential to consider the age of receiving hearing aids and parental involvement in intervention as the most important factors in children's education and designing treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that some children with cochlear implants are even able to learn language more quickly than the average child with normal hearing and therefore 'catch up' some of the delay in language acquisition incurred before they received a cochlear implant, with reports of language development at age-appropriate levels between the ages of 4 and 7 years (Yoshinaga-Itano et al, 2010). As with speech perception and speech production, there is still enormous variation in language skills between individuals and between different populations of children (Spencer et al, 2003), with recent reports still documenting many children with significant language delays (Ching, 2010;Connor et al, 2000;Sarant et al, 2009;Young & Killen, 2002).…”
Section: Language Developmentmentioning
confidence: 99%